(untitled) (Research, Society and Development, 2021)
Objective: to measure the critical thinking capacity of medical students at a Brazilian institution from the PC domains and throughout the stages of the course. Methodology: The sample consisted of 312 medical students regularly enrolled at a University in the state of São Paulo, Brazil. The study participants were asked to apply the Watson-Glaser Critical Thinking Appraisal III (WG-III) instrument to assess the students’ critical thinking skills, in addition to the sociodemographic questionnaire. Descriptive analysis was used for sociodemographic data and for critical thinking scores, in addition to comparative analysis between students from different years of the course. and categorized in the RED sphere, follows the trend of average performance indicated by the domains: Recognize Assumptions (50.61), Evaluate Arguments (50.62) and Draw Conclusions (50.41). The comparative analysis of the data points out that there was no significant difference as a pattern that demonstrates the positive displacement of critical thinking according to students from different stages of the course. ANOVA points out only punctual statistical differences in performance for the 2nd and 4th stages. Conclusion: the critical thinking of the sample studied is below the expectations projected for medical students, the performance in the test shows that the pedagogical strategies of the medical career and the academic perspectives of the students do not seem to have a determining role in the acquisition or improvement of critical thinking.